Calculating the inductive electric field in the terrestrial magnetosphere. Issue 5 (24th May 2017) - Ilie, Raluca; Daldorff, Lars K. S.; Liemohn, Michael W.; Toth, Gabor; Chan, Anthony A.
Abstract: This study presents a theoretical approach to calculate the inductive electric field, and it is further applied to global MHD simulations of the magnetosphere. The contribution of the inductive component to the total electric field is found by decomposing the motional electric field into a superposition of an irrotational and a solenoidal vector and assuming that the time‐varying magnetic field vanishes on the boundary. We find that a localized change in the magnetic field generates an inductive electric field whose effect extends over all space, meaning that the effect of the inductive electric field is global even if the changes in the magnetic field are localized. Application of this formalism to disturbed times provides strong evidence that during periods of increased activity the electric field induced by the localized change in magnetic field can be comparable to (or larger than) the potential electric fields in certain regions. This induced field exhibits significant spatial and temporal variations, which means that particles that drift into different regions of space are being exposed to different means of acceleration. These results suggest that the inductive electric field could have a substantial contribution to particle energization in the near‐Earth region even though the changes in the magnetic fields occur at distances of several tens of Earth radii. This finding is particularly important for ring current modeling which in many cases excludes inductive contributions to the total particle drift. Key Points: Theoretical approach to calculating the inductive electric field The effect of the inductive electric field is global even if the changes in B are localized Inductive electric field contributes notably to the total electric field in the near‐Earth region